2015
DOI: 10.4028/www.scientific.net/amr.1115.517
|View full text |Cite
|
Sign up to set email alerts
|

Mode I Stress Intensity Factor for a Cracked Plate with an Integrated Piezoelectric Actuator

Abstract: The fracture performance of cracked structures is dominated by singular stress in the crack tip vicinity. In fracture mechanics most interest is focused on stress intensity factors, which describe the singular stress field ahead of a crack tip and govern fracture of structures when a critical stress intensity factor is reached. In the present work linear fracture mechanics is applied in order to obtain the fracture toughness parameters of a cracked plate integrated with piezoelectric actuator under mode I load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…In recent studies, Abuzaid et al [ 2 , 96 , 97 , 98 , 99 , 100 ] used piezoelectric material to control the damage propagation in aerospace structures. The ideas were developed to produce compression/tension stress around the damaged area along with the width of the piezoelectric actuator.…”
Section: Discussion and Critical Reviewsmentioning
confidence: 99%
“…In recent studies, Abuzaid et al [ 2 , 96 , 97 , 98 , 99 , 100 ] used piezoelectric material to control the damage propagation in aerospace structures. The ideas were developed to produce compression/tension stress around the damaged area along with the width of the piezoelectric actuator.…”
Section: Discussion and Critical Reviewsmentioning
confidence: 99%
“…In recent investigations, Abuzaid et al [86][87][88][89][90][91] utilized the piezoelectric actuator (PIC 151) to control the crack propagation in aluminum rectangular thin plates and they determined the fracture parameters, such as stress intensity and stress concentration factors. The ideas developed to produce stress (compression/tension) on the stress distribution around the hole and along with the width of the damaged plate by the piezoelectric actuator.…”
Section: Active Controlmentioning
confidence: 99%
“…The study on repair based on the boundary element method was developed by Alaimo et al (2009Alaimo et al ( , 2011. An approximate analytical derivation for Mode-I, restricted to the application of square actuator and without accounting for the singularity of the stress at the crack tip, was carried out by Abuzaid et al (2015b). An investigation to study the influence of adhesive properties on active repair under Mode-I fracture (Abuzaid et al, 2015a) showed that a higher adhesive shear modulus is desired for repairing cracks, as it allows the transfer of the stress induced by the piezoelectric actuator to the host structure.…”
Section: Introductionmentioning
confidence: 99%